Hervé Lanotte, Investissements publicitaires et choix contractuels d’approvisionnement : les clés d’une gouvernance « coopérative » dans la filière des vins de Champagne - Hervé Lanotte (Revue de la Régulation)
This thesis takes as its cue the simple observation that advertising investments by Champagne firms are key to upholding the Champagne PDO (Protected Designations of Origin, AOC), and develops a line of reasoning according to which these investments are one of the features that explain the stable and successful governance within the industry. The advertising efforts of the Champagne merchants, beyond their purely commercial aspect, are actually part of an overall scheme to guarantee the signing of multi-annual upstream-downstream supply contracts put into place in the mid-twentieth century by the whole profession. Without requiring explicit commitments to, or advertising cost sharing with the merchant on the part of the wine grower, this strategy makes possible a collective inter-professional dynamic relationship that underpins vertical cooperation. To justify this conjecture, we propose a diachronic reading of the way this local and cooperative governance arose. This new interpretation sheds light on the complexity of guarantee mechanisms and on the major role of the merchants' advertising investments. We go on to consider a taxonomy in order the forms of advertising with regard to their spillover effects and the way they are implemented. At this point, we show how the advertising strategy of the Champagne firms can be assimilated to cooperative advertising. We conclude this thesis with a model that reflects the real impact of advertising investment on choices of supply contract, choices that are characteristic of the singular nature of the vertical relation in Champagne. Various types of contracts are thus modelled so as to understand the effects of such advertising. We show that the grape growers’ restricted bargaining power and the limited residual effect of advertising on the market of grape growers' direct sales of champagne wine could lead them to put into question these long-term supply contracts.